2020
DOI: 10.1021/acs.jpcb.0c04382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silane Monolayers on the Adsorption of Streptavidin on Silica and Its Subsequent Interactions with Biotin: Molecular Dynamics and Steered Molecular Dynamics Simulations

Abstract: Protein adsorption on surfaces is used in analytical tools as an immobilization mean to trap the analyte to be detected. However, protein adsorption can lead to a conformational change in the protein structure, resulting in a loss of bioactivity. Here, we study the adsorption of the Streptavidin -Biotin complex on amorphous SiO 2 surfaces functionalized with five different silane selfassembled monolayers by all-atom Molecular Dynamics simulations. We find that the Streptavidin global conformational change incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 58 publications
6
41
0
Order By: Relevance
“…Firstly, despite the same conditions, the different initial orientations lead to significantly different trajectories of the protein, with predominantly low d values in some cases whereas predominantly high d values were obtained in other cases. The dominant influence of initial orientation agrees with earlier simulation studies of different proteins 30,49,53 . Secondly, although electrostatic considerations would imply greater lysozyme–membrane affinity than that of α‐lactalbumin, the d values for lysozyme do not appear to be distinctly smaller.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Firstly, despite the same conditions, the different initial orientations lead to significantly different trajectories of the protein, with predominantly low d values in some cases whereas predominantly high d values were obtained in other cases. The dominant influence of initial orientation agrees with earlier simulation studies of different proteins 30,49,53 . Secondly, although electrostatic considerations would imply greater lysozyme–membrane affinity than that of α‐lactalbumin, the d values for lysozyme do not appear to be distinctly smaller.…”
Section: Resultssupporting
confidence: 86%
“…Because of the variation of the nature of the residues throughout the protein, the interaction energies depend on which residues are oriented so that they are able to interact with the membrane 31,52,53 . Depending on the orientation of the protein, metastable states are known to be attained instead of the minimum energy state 54 .…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the large size and structural heterogeneity of lysozyme, different initial orientations of the lysozyme were considered, since it is well‐acknowledged that initial orientation affects adsorption behavior 55,56 . Regarding capturing representative orientations, an earlier study suggested 90° orientations 57 . In this study, six initial orientations were used, because too few may not be sufficiently representative particularly in view of metastable states, 35 while too many would incur high computational costs.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, six initial orientations were used, because too few may not be sufficiently representative particularly in view of metastable states, 35 while too many would incur high computational costs. As illustrated in Figure 1, other than the orientation shown (i.e., as downloaded from the PDB and designated a x = 0°, a y = 0°), three additional rotations about the x ‐axis (i.e., a x = 90°, a y = 0°; a x = 180°, a y = 0°; and a x = 270°, a y = 0°) and two additional rotations about the y ‐axis (i.e., a x = 0°, a y = 90°; and a x = 0°, a y = 270°) were investigated 57 . For the quantification of parameters such as interaction energy or rotational angle, the average value was taken from these six runs.…”
Section: Methodsmentioning
confidence: 99%